Analysis of Different Cracked on Cantilever Beam Using Ansys Software - Sivaraman, Mahalechumi; Zaleha Mohamad (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A cantilever beam is a rigid structural element supported at one end and unbalanced at the other. Cantilever beams are commonly used in construction to support balconies, roofs, and other overhangs. This investigation focused on analyzing the impact of crack depth and location on the natural frequency of cantilever beams made of mild steel, aluminum, and stainless steel. The study considered beams with a length of 3m, width of 0.25m, and depth of 0.20m, employing modal analysis to examine the first three modes of transverse vibration for cracked beams. Cracks were located at 0.5m, 1.5m, and 2.5m from the fixed end on both the top and bottom surfaces, with a fixed depth and width of 0.002m and 0.1m, respectively. Finite Element Analysis (FEA) simulations using Ansys software revealed that the natural frequency of cracked beams decreased compared to uncracked ones. Mild steel consistently exhibited slightly higher natural frequencies than aluminum and stainless steel, suggesting its superior performance in terms of crack resistance, deformation control, and suitability for fixed-end beam applications.